CoP@Ni2P microcrystals in situ grown on carbon fiber as counter electrode catalysts for high-efficiency dye-sensitized solar cells. (December 2022) - Du, Y.; Shen, Z.; Yue, G.; Gao, Y.; Huo, J.; Dong, C.; Tan, F.
Abstract: Transition metal phosphides (TMPs) have recently emerged as outstanding energy conversion and storage materials for their highly active surface sites, electrical conductivity, and thermal and structural stability. However, TMPs as the counter electrode (CE) of dye-sensitized solar cells (DSSC) are rarely reported. Here, cobalt phosphide and nickel phosphide (CoP@Ni2 P) microcrystals were successfully prepared in situ grown on carbon fiber of carbon paper (CP) by using simple hydrothermal and phosphating methods, and served as CE in DSSCs. The CP acted as a supporting conductivity substrate and an electron transport "speedway, " which can enhance the electrocatalytic ability of CE and photoelectric conversion efficiency of the devices. The cells based on CoP@Ni2 P@CP CE with 1 mmol NiCl2 ·6H2 O deliver a power conversion efficiency of 8.33%, which is superior to that of state-of-the-art Pt-based cell (7.54%). Moreover, the CoP@Ni2 P@CP CE also displays a small charge transfer resistance (2.07 Ω cm 2 ) at the interface between electrolyte and CE, as well as prefect electrochemical catalytic stability in I − /I3 − electrolyte. These findings indicate that the CoP@Ni2 P@CP CE possesses outstanding electrocatalytic and photoelectric conversion performance along with desired stability to be utilized as an efficient Pt-free alternative in DSSCs. Graphical abstract: Image 1 Highlights: The design strategy of introducing partners can improve the electrochemical performance of the counter electrode. The CP@NP@CP-3 electrode shows more excellent catalytic activity as well as Pt. The DSSC with CP@NP@CP-3 CE achieves a high-power conversion efficiency of 8.33%.